Membangun Direktori Publikasi Karya Ilmiah Melalui Jaringan Cloud Perpustakaan Universitas Riau - Yasin Setiawan; Evi Susanti (Jurnal Gema Pustakawan, 2021)
The purpose of this research is to build a system with a scientific paper directory service, namely a directory of journal articles published by the University of Riau which is organized in such a way that it is easy to search. The design is carried out through the stages of system design analysis, global design and detailed design. The scientific work directory system of the Riau University Library which can be accessed online at the address https://cloud.unri.ac.id/direktori. The development carried out in this study uses the stages of system design, system development, implementation and evaluation, with the final result of a web-based interface.